Public Health Approaches to Infection Control in Intensive Care Units - Alenazi, Menawer Sayaah Menawer; Alanazi, Hind Atallah Ramadan; Alanazi, Alhanoof Atallah Ramadan; Alharbi, Mona Abdulrhman Ali; Alshammari, Manal Khairallah A.; Mokeli, Ali Hamod Haidar; Homdi, Samer Alhassan Salwi; Alharbi, Essa Saad Mutlaq; Mawkili, Alhassan Hassan Arar; Refaei, Yahya Ali Mohammed; et al. (Journal of Posthumanism, 2024)
Intensive Care Units (ICUs) are critical care areas with increased infection control requirements as they have populations particularly vulnerable to Health-Care Associated Infections (HCAIs). Prevention of these infections is difficult due to patient comorbidities, antimicrobial use, and increased contact with healthcare workers. A public health approach to infection control uses the control of transmission as an exemplar to demonstrate how a population focus can benefit infection control and prevention in ICUs, extending the scope of practice for nurses. Infection control is a field involved in defining and managing risk factors for infection and is regarded as a key method to interrupt HCAIs in ICUs, emphasizing the need for extractable generalizable principles and avoidance of facility reliance (Datta et al., 2014). Both the Centers for Disease Control and Prevention (CDC) and World Health Organization (WHO) provide general guidelines on infection control with a population focus. The role for nursing in ICUs includes remaining up-to-date with these guidelines and emphasizing leadership and advocacy roles to benefit patients by implementing effective infection control strategies (see subsequent sections for details of nursing responsibilities). Environmental analyses offer the potential to help reduce the risk of HCAIs in ICUs by indentifying locations with a greater risk of contamination. The use of diagnostics and autopsies, frequently under-utilized in developing countries where risk is often higher, also provides the opportunity to improve patient safety for individuals with HCAIs. Given these challenges, large-scale multicentre studies are required to determine the extent of HCAIs in these regions and to encourage the implementation of basic infection control measures. In India, specific problems are complicated by the increased incidence of infections within the community, which leads to the rapid colonization of resistant bacteria following admission to an ICU. Efforts to decrease morbidity and mortality also need to address the wider community and historical National Laboratory Surveillance data suggest a current increase in antibiotic resistance across Europe. In the ICU, the importance of antimicrobial stewardship and the primary cause of excess mortality underscore the need for continued antibiotic development. The example of European influenza points to the lasting effects of staffing and healthcare provision on HCAI in ICUs.